STRANGE ATTRACTORS IN MAGMAS: EVIDENCE FROM LAVA FLOWS - Poli G.; Perugini D. (My University, 2002)
Magma mixing structures from three different lava flows (Salina, Vulcano and Lesbos) are studied in order to assess the possible chaotic origin of magma mixing processes. Structures are analysed using a new technique based on image analysis procedures that extract time series that are representative of the relative change in composition through the structures. These time series are then used to reconstruct the attractors underlying the magma mixing process and to calculate the fractal dimension of the attractors. Results show that attractors exist and possess fractional dimensions. This evidence suggests that the mixing of magmas is a chaotic process governed by a low number of degrees of freedom. In addition, fractal dimension analyses allows us to discriminate between different regimes of mixing in the three lava flows. In particular our analyses suggest that the lava flow of Salina underwent more turbulent mixing than the lava flows of Lesbos and Vulcano.
Keywords: MAGMA MIXING; TIME SERIES; STRANGE ATTRACTORS; CHAOTIC DYNAMICS